1999
DOI: 10.1111/j.1558-5646.1999.tb04518.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Performance and Sex‐ratio Evolution in a Dioecious Plant

Abstract: Abstract.-There has been a proliferation of studies, in a variety of taxa, that have detected sex-linked or cytoplasmic genes that enhance their own transmission via sex-ratio distortion. One of the most important parameters influencing the dynamics of these elements is the magnitude of their transmission advantage. In many systems, the mechanism of sex-ratio distortion is to abort X-or Y-bearing gametes. With this mechanism, the transmission advantage associated with sex-ratio distortion is diminished when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 95 publications
4
33
0
Order By: Relevance
“…Our results on the influence of population size, plant density, and the composition of the local mating neighborhood in R. hastatulus highlight the interaction of ecology, demography, and genetics for sex-ratio variation. Although the importance of certation has been controversial (Carroll and Mulcahy 1993;Taylor et al 1999), our study provides further evidence in support of the hypothesis that this mechanism contributes toward female-biased sex ratios.…”
Section: Discussionsupporting
confidence: 84%
“…Our results on the influence of population size, plant density, and the composition of the local mating neighborhood in R. hastatulus highlight the interaction of ecology, demography, and genetics for sex-ratio variation. Although the importance of certation has been controversial (Carroll and Mulcahy 1993;Taylor et al 1999), our study provides further evidence in support of the hypothesis that this mechanism contributes toward female-biased sex ratios.…”
Section: Discussionsupporting
confidence: 84%
“…High quantity pollen (pollen mixture from several males) could produce more female progeny than low quantity pollen (pollen from a single male) [16]. Similar results were also found in the dioecious herb Rumex nivalis, where stronger female-biased sex ratio progeny were presented with maternal parents closer to the males due to the pollen tube competition [17].…”
Section: Discussionsupporting
confidence: 69%
“…Sex-biased herbivory might also create a biased sex ratio [13], [14], [15]. Other studies of progeny sex ratios have observed that pollen competition might produce different sex ratios in offspring [16]. High stigmatic pollen loads can induce pollen tube competition and produce stronger female-biased seed sex ratios [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although primary sex ratios in S. latifolia are often female biased, the degree of bias is far less pronounced in comparison with Rumex (Carroll and Mulcahy 1993;Taylor 1994). In controlled crosses males produce heritable differences in sex ratios ranging from slightly male biased to strongly female biased (Taylor 1994(Taylor , 1999Taylor et al 1999;Ingvarsson and Taylor 2002). This heritable variation is unlikely to be subject to environmental modification in a manner similar to the way that pollination conditions alter sex ratios in Rumex.…”
Section: General Patterns and Mechanismsmentioning
confidence: 97%
“…Meiotic drive or segregation distortion can result in the selective abortion of male-determining gametes resulting in a bias in the frequency of female-determining gametes (Taylor and Ingvarsson 2003). Segregation distortion has been detected in Silene latifolia (Taylor 1994(Taylor , 1999Taylor et al 1999;Ingvarsson and Taylor 2002), the other well-studied dioecious species with heteromorphic sex chromosomes (Charlesworth 2002). Although primary sex ratios in S. latifolia are often female biased, the degree of bias is far less pronounced in comparison with Rumex (Carroll and Mulcahy 1993;Taylor 1994).…”
Section: General Patterns and Mechanismsmentioning
confidence: 99%